Research progress on the role of the Wnt signaling pathway in pituitary adenoma - Wang, Wencai; Ma, Luyao; Zhao, Yongqiang; Liu, Menghao; Ye, Wei; Li, Xianfeng (Frontiers in Endocrinology, 2023)
Pituitary adenoma (PA) is the third most common central nervous system tumor originating from the anterior pituitary, but its pathogenesis remains unclear.The Wnt signaling pathway is a conserved pathway involved in cell proliferation, Selfrenewal of stem cells, and cell differentiation. It is related to the occurrence of various tumors, including PA. This article reviews the latest developments in Wnt pathway inhibitors and pathway-targeted drugs. It discusses the possibility of combining Wnt pathway inhibitors with immunotherapy to provide a theoretical basis for the combined treatment of PA.